2016
DOI: 10.1080/21505594.2016.1250996
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence ofVibrio mimicusstrain SCCF01 with potential application in fish vaccine development

Abstract: Vibrio mimicus strain SCCF01 was isolated from the yellow catfish (Pelteobagrus fulvidraco) during a mass mortality event at an aquaculture facility. We sequenced the genome of strain SCCF01, then predicted possible effective targets for subunit vaccine and identified possible virulence genes for live attenuated vaccine. The genome of SCCF01 consists of 2 circular chromosomes of 3,213,040 and 1,272,975 bp with G+C content of 46.61% and 45.88%, respectively. Subcellular localization, number of transmembrane hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Challenges showed that bath immersion of strain SCCF01 (10 [6] CFU·mL −1 ) caused 100% mortality of yellow catfish. The whole-genome sequence of V. mimicus was obtained by single-molecule real-time (SMRT) sequencing using platform PacBio RS II [12]. The complete genomic sequences of SCCF01 have been deposited in GenBank under the accession numbers CP016383 (chromosome I) and CP016384 (chromosome II).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Challenges showed that bath immersion of strain SCCF01 (10 [6] CFU·mL −1 ) caused 100% mortality of yellow catfish. The whole-genome sequence of V. mimicus was obtained by single-molecule real-time (SMRT) sequencing using platform PacBio RS II [12]. The complete genomic sequences of SCCF01 have been deposited in GenBank under the accession numbers CP016383 (chromosome I) and CP016384 (chromosome II).…”
Section: Methodsmentioning
confidence: 99%
“…Since 2011, large-scale V. mimicus infectious outbreaks have occurred continuously in Siluriformes farms in China. V. mimicus strain SCCF01, which is a highly virulent strain isolated from yellow catfish (Pelteobagrus fulvidraco) in China, causes almost 100% mortality in yellow catfish [9,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifications of several possible virulence genes have been made in order to determine the complete genome sequence of V. mimicus strain sccf01 related to yellow catfish infection, which contributed to the development of subunit and lives attenuated vaccines by providing a genetic basis. Moreover, the immersion challenge test depicted that strain SCCF01 can adhere and colonize the mucosal surface, which is hopeful for the development of an attenuated vaccine [ 89 ].…”
Section: Control and Prevention Strategies Of Vibriosmentioning
confidence: 99%
“…In addition to its well-established role in regulating virulence factors, the Crp-cAMP complex has been implicated in regulating various activities, including motility ability [17], biofilm formation [18], host colonization [19], pheromone signaling [20], natural competence [21], osmotolerance [22], lipopolysaccharide modifications [23], resistance to bacteriophages [24], and integrase activity [25]. The crp gene has been identified in whole genome sequencing of SCCF01 by our laboratory [26]. Nevertheless, the current knowledge of V. mimicus is still limited.…”
Section: Introductionmentioning
confidence: 99%